Melphalan as a Promising Treatment for BRCA-Related Ovarian Carcinoma - Conteduca, Vincenza; Scarpi, Emanuela; Farolfi, Alberto; Brighi, Nicole; Rossi, Lorena; Gurioli, Giorgia; Lolli, Cristian; Schepisi, Giuseppe; Bleve, Sara; Gianni, Caterina; Virga, Alessandra; Altavilla, Amelia; et al. (Frontiers in Oncology, 2021)
Introduction Melphalan, as a bifunctional alkylating agent has been shown to be selectively efficient in BRCA-deficient case reports of epithelial ovarian cancer (EOC). The clinical benefit of melphalan on unselected platinum-resistant EOC population and stratified by BRCA status has not been clearly elucidated. We aimed to determine the response to melphalan in patients with recurrent EOC after platinum-based therapy. Material and Methods This retrospective observational study included patients with recurrent EOC treated with melphalan between February 2007 to July 2020. Eligibility criteria included having a histological confirmation of EOC, previous treatment with carboplatin plus paclitaxel regimens, and disease recurrence during treatment with or within 6 months of the end of the platinum-based chemotherapy. Results A total of 75 platinum-resistant EOC patients were enrolled. Median age was 69 years (range 41-82). Median of previous therapies before melphalan was 4 (range 1-7). We observed a median follow-up of 32 months (range 1-62), progression-free survival (PFS) and overall survival (OS) of 3.6 months (range 2.9-4.7) and 9.5 months (range 8.0-14.1), respectively. In the whole population, 1 complete response, 6 partial responses and 37 stable diseases were registered with an overall clinical benefit rate of 58.7%. In BRCA1/2 mutant patients, we showed a significant longer PFS compared to BRCA1/2 wild type patients (6.2 versus 2.6 months; hazard ratio (HR) 0.25, 95% confidence interval (CI) 0.10-0.61; p=0.002). Moreover, a trend was seen for BRCA1/2 mutants to have a better OS (25.9 versus 8.0 months; HR 0.38; 95% CI 0.12-1.19; p=0.097). Conclusions Our study represents the largest cohort of heavily-pretreated EOC patients receiving melphalan treatment. Here, we report a considerable clinical activity of melphalan chemotherapy, more evident in a subset of BRCA1/2 mutated patients. Prospective studies to validate these findings are warranted.